2022
DOI: 10.3390/economies10050110
|View full text |Cite
|
Sign up to set email alerts
|

Committees or Markets? An Exploratory Analysis of Best Paper Awards in Economics

Abstract: Despite the general usefulness of citations as a sort of test of the value of one’s work in the marketplace of ideas, journals and publishers tend to use alternative bases of judgment, namely committees, in selecting candidates for the conferral of journals’ best paper awards. Given that recognition—sometimes in the form of compensation and on other occasions in the form of awards—in academe is geared toward incentivizing the production of impactful research and not some less desirable goal or outcome, it is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Studies in Computer Science [ 39 ] and Ecology and Evolution [ 11 ] have revealed opaque award criteria and processes. In Economics, a study has found a mismatch between subjective jury decisions and article citation impacts, similar numbers of men and women among the winners, and affiliations dominated by the United States institutions [ 40 ]. In Engineering, most winning authors were not native English speakers [ 41 ].…”
mentioning
confidence: 99%
“…Studies in Computer Science [ 39 ] and Ecology and Evolution [ 11 ] have revealed opaque award criteria and processes. In Economics, a study has found a mismatch between subjective jury decisions and article citation impacts, similar numbers of men and women among the winners, and affiliations dominated by the United States institutions [ 40 ]. In Engineering, most winning authors were not native English speakers [ 41 ].…”
mentioning
confidence: 99%
“…For instance, this is the case in Computer Science 33 . In Economics, studies have found a notable mismatch between subjective jury decisions and article citation impacts, similar numbers of men and women among the winners, and affiliations dominated by the US institutions 34 . In Engineering journal awards, most winning authors were not native English speakers 35 .…”
mentioning
confidence: 99%